La filiera del tartufo e la sua valorizzazione in Toscana e Abruzzo - Marone, Enrico (Proceedings e report, 2011)
There can be no valorisation of the truffle system without a sufficient awareness of the chain that brings the truffle from the ground to the consumer. This in fact renders explicit the link between the product and the territory of origin, eliminating disparities at the level of information between the consumer and the gatherer/producer/transformer. In this case, the value of the product is increased to the extent that along with it we also acquire the quality of the environment that produces it. The research that is presented in this volume offers valid elements of orientation, both for those working in the sector and for the public sector, to which it offers knowledge useful for the defence of the local product and for guiding sector policies.